2007
DOI: 10.1186/1471-2474-8-81
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic and muscular responses and recovery to one-hour laboratory mental stress in healthy subjects

Abstract: Background: Stress is a risk factor for musculoskeletal pain. We wanted to explore stress related physiology in healthy subjects in order to gain insight into mechanisms of pain development which may relate to the pathophysiology of musculoskeletal pain disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 40 publications
4
35
0
4
Order By: Relevance
“…During these measurements, the physical load was a 45°shoulder abduction, which was a much heavier physical load compared to the mental load in that study and to the physical load in the present study. The shift toward a slightly higher instantaneous HF frequency during MT can probably be related to a higher respiration frequency, as the main peak in the HF band is normally caused by respiration (Stevenson and Ripley 1952;Nilsen et al 2007). An increased respiration frequency during a 1-h low-grade mental stress task in healthy subjects was already found in Nilsen et al (2007).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…During these measurements, the physical load was a 45°shoulder abduction, which was a much heavier physical load compared to the mental load in that study and to the physical load in the present study. The shift toward a slightly higher instantaneous HF frequency during MT can probably be related to a higher respiration frequency, as the main peak in the HF band is normally caused by respiration (Stevenson and Ripley 1952;Nilsen et al 2007). An increased respiration frequency during a 1-h low-grade mental stress task in healthy subjects was already found in Nilsen et al (2007).…”
Section: Discussionmentioning
confidence: 98%
“…The shift toward a slightly higher instantaneous HF frequency during MT can probably be related to a higher respiration frequency, as the main peak in the HF band is normally caused by respiration (Stevenson and Ripley 1952;Nilsen et al 2007). An increased respiration frequency during a 1-h low-grade mental stress task in healthy subjects was already found in Nilsen et al (2007). Vlemincx et al (2011) also reported an increased breathing rate during mental stress, although Bernardi et al (2000) in contrast observed a slowing down of respiration frequency.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have examined the physiological measures of heart rate, blood pressure and cortisol levels during mentally stressful tasks. Hjortskov et al (2004), Johnston et al (2008) and Nilsen et al (2007) reported signiWcant increases in heart rate and respiration frequency after mentally stressful tasks. Garde et al (2002) and Wahlström et al (2002) found that blood pressure increased when a mental stressor was added to the computer tasks.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have attempted to examine the eVects of mental workload or mental stressors on muscle activation during diVerent forms of computer work, which included Weld investigations (Hägg and Aström 1997;Rissén et al 2002;Vasseljen and Westgaard 1995;Wahlström et al 2003) and laboratory studies (Bansevicius et al 1997;Blangsted et al 2004;Finsen et al 2001;Hughes et al 2007;Johnston et al 2008;Krantz et al 2004;Leyman et al 2004;Lundberg et al 2002;McLean and Urquhart 2002;Nilsen et al 2007;Schleifer et al 2008;Van Galen et al 2002;Visser et al 2004). Many of these studies aimed to diVerentiate the eVects due to physical and mental workloads.…”
Section: Introductionmentioning
confidence: 97%
“…Headache patients also filled in headache diaries for the same period. Every subject answered several questionnaires including: Epworth Sleepiness Scale (13), questions adapted from Karolinska Sleep Questionnaire (14), Pittsburgh Sleep Quality Index (PSQI) (15), Hospital Anxiety and Depression Subscales (16), and 10 questions from the Autonomic Symptom Profile (17,18). As a supplement to the Epworth (4)).…”
Section: Methodsmentioning
confidence: 99%